ELEKTRİKLE UYARILAN İZOLE KOBAY VE FARE SOL ATRİYUMU VE SIÇAN DİYAFRAMININ KASILMASI ÜZERİNE KALSİTONİN’İN ETKİLERİ - AŞKIN, Çiğdem; BARLAS, Aydın; KÜÇÜKHÜSEYİN, Cihat (Cerrahpaşa Medical Journal, 2019)
Background.- Although the regulatory role of calcitonin released from the parafolicular cells of thyroid gland and plays essential role in the haemoestasis of blood Ca2+ was well documented, its effects on the physiological functions of tissues except bones is not as yet fully established. Therefore, the aim of this study was to explore, how calcitonin act on the contractile activity of heart and striated muscle. Design and Results.- Experiments were carried out on the isolated electrically driven left atria of guinea-pigs and mice and phrenic nerve-diaphragm preparations of rats. In the electrically driven guinea-pig left atria (1 Hz, 2 msec, 2x threshold voltage), contractility was depressed by ampule calcitonin (miacalcic) in a dose-dependent manner at concentrations in range of 0.25-4 mg/ml. This effect of ampule calcitonin was weaker with respect to those produced by the solvent being in the same size. Especially at 2 and 4mg/ml of ampule calcitonin, the contractile response was biphasic, e.g. an initial short-lived positive inotropic effect was preceding the main negative inotropic one. Theophylline (0.5 mM), atropine (2 mg/ml) and methylene blue (2 mg/ml) antagonized ampule calcitonin nonsignificantly, whereas the effect of solvent remained unaltered. Verapamil (0.5 mg/ml), however, augmented the negative inotropic effect of both ampule calcitonin and the solvent. In the phrenic nerve-diaphragm preparation, although contractions induced by direct electrical stimulation (0.1 Hz, 5 msec, 2x threshold voltage) was depressed by ampule calcitonin dose-dependently in a concentration range of 1-8 mg/ml, contractions induced by nerve stimulation (0.1 Hz, 1 msec, 2x threshold voltage) was augmented over a concentration of 4 mg/ml. Conclusion.- Depending on these findings, it was concluded that calcitonin has a stimulatory effect on the contractile function of heart and striated muscle which is masked by the solvent and that cAMP, cGMP and Ca2+ channels all appeared to involve in the cardiac effects of the test agent.